2010
DOI: 10.1371/journal.pone.0012140
|View full text |Cite
|
Sign up to set email alerts
|

SMA CARNI-VAL Trial Part I: Double-Blind, Randomized, Placebo-Controlled Trial of L-Carnitine and Valproic Acid in Spinal Muscular Atrophy

Abstract: BackgroundValproic acid (VPA) has demonstrated potential as a therapeutic candidate for spinal muscular atrophy (SMA) in vitro and in vivo.MethodsTwo cohorts of subjects were enrolled in the SMA CARNIVAL TRIAL, a non-ambulatory group of “sitters” (cohort 1) and an ambulatory group of “walkers” (cohort 2). Here, we present results for cohort 1: a multicenter phase II randomized double-blind intention-to-treat protocol in non-ambulatory SMA subjects 2–8 years of age. Sixty-one subjects were randomized 1∶1 to pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
123
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(129 citation statements)
references
References 35 publications
2
123
0
4
Order By: Relevance
“…27,[29][30][31] However, the clinical benefit of the substances tested to date remains uncertain. 21,[32][33][34][35] A complete rescue of the phenotype by HDACi application is unlikely to be achieved for patients most severely affected and only possessing a low number of SMN2 copies, and thereby restricted potential for increase in FL protein expression. Nonetheless, improvement of quality of life is still an objective worth investigating for these patients.…”
Section: Introductionmentioning
confidence: 99%
“…27,[29][30][31] However, the clinical benefit of the substances tested to date remains uncertain. 21,[32][33][34][35] A complete rescue of the phenotype by HDACi application is unlikely to be achieved for patients most severely affected and only possessing a low number of SMN2 copies, and thereby restricted potential for increase in FL protein expression. Nonetheless, improvement of quality of life is still an objective worth investigating for these patients.…”
Section: Introductionmentioning
confidence: 99%
“…The use of HDAC inhibitors has been well advanced in the field of cancer, with many tested in clinical trials, and three approved for cancer therapy (reviewed in Mottamal et al 2015). Phase II clinical trials for the use of HDAC inhibitors for the treatment of the motor neuron disease, spinal muscular atrophy (SMA), yielded initial encouraging results, although these were not confirmed or extended by later studies (Mercuri et al 2004(Mercuri et al , 2007Swoboda et al 2010;Kissel et al 2011Kissel et al , 2014. More research on the specific targets of acetylation, the specific enzymes involved, and the development of more directed compounds are likely required.…”
Section: Establishing a Modelmentioning
confidence: 99%
“…To date, the 26 clinical trials that have investigated the effect of 12 potential treatments in patients with SMA have failed to show benefit owing to a number of factors, yet have enabled expertise in trial design to be developed [106,107]. Experience has suggested that younger patients might be more responsive to treatment [107,108]. Older patients may be refractive to treatment because they have been living with their disease for longer periods of time or because critical tissues have been irreversibly damaged.…”
Section: Challenges Is Smn1-related Sma Therapeuticsmentioning
confidence: 99%